FAKTOR YANG BERPENGARUH TERHADAP PERILAKU KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Empiris Di KPP PRATAMA Semarang Tengah 1) - Nur Haini Ningsih, 11.05.52.0028; Badjuri, Achmad (Students Journal of Accounting and Banking, 2015)
This study aims to analyze empirically the Public Justice Perceptions and distribution of the Tax Burden, Reciprocal Government, Special Provisions, Tax Rate Structure Preferred, Personal Interests and Sanctions Against Tax Compliance Behavior individual taxpayer (WPOP) in KPP Central Semarang One. The population in this study is the individual taxpayer (WPOP) in KPP Central Semarang One and already have a TIN. In this study, the sample is WPOP having a trading business and work freely. Sampling was done by using purposive sampling method and sample size were 116 questionnaires. Data were analyzed using multiple linear regression model. The results showed that public justice and the distribution of the tax burden, government reciprocity, special provisions, structure preferred rates, and personal interests significantly influence the behavior of an individual taxpayer compliance (WPOP). While tax penalties not significantly affect the behavior of an individual taxpayer compliance (WPOP).Keywords: Perception of General Fairness and Distribution of Tax Burden, Exchange With The Government, Special Provisions, Preffered Tax Rate Structure, Self Interests, Sanctions Tax Compliance, and Behavior Personal Taxpayers